Communication of bad news in pediatrics: integrative review - Bruna Pase Zanon; Luiza Cremonese; Aline Cammarano Ribeiro; Stela Maris de Mello Padoin; Cristiane Cardoso de Paula (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to identify the scientific evidence of the elements of communication in the process of communicating bad news in pediatrics. Methods: integrative review searched in the LILACS, PubMed and WoS databases. Primary studies in Portuguese, Spanish or English were included. Results: the evidence from the 40 studies were organized according to the elements of communication: sender (family and/or professional), receiver (family and/or child), message (bad or difficult news about diagnosis/prognosis; empathetically, honestly, objective, hopeful and available), channel (materials, quality, quantity and pace), context and effects (social and emotional changes), noise (feelings and language) and failures (silencing and misleading information). Conclusions: there is a need to prepare the institution and team, as well as the family and the child, in order to promote co-responsibility in this process, to minimize suffering and communication noise and to avoid failures, recognizing the child's right to know their condition.